Chemical and Organoleptic Quality of Free-Gluten Dry Noodles from Sorghum (Sorghum bicolor) and Modified Cassava Flour with Different Drying Temperature - Fadjar Kurnia Hartati; Nunuk Hariyani; Ayyu Nisa’ Rizky N.F. (CV. Media Digital Publikasi Indonesia, 2023)
Dry noodles are widely commercialized thanks to their durability and practicality for consumption as side dishes or staples to replace rice. The development of dry noodles is robustly conducted, mainly by substituting its main ingredient of wheat flour to local staple flour with similar or better nutritional value and characteristics compared to wheat flour and gluten-free as well. Some alternatives are sorghum (Sorgum bicolor) flour and mocaf (Modified cassava flour). Applying the correct drying temperature to produce dry noodles with good chemical and organoleptic quality. This research utilized a factorially formulated Completely Randomized Design with three levels for each actor. The first factor is the sorghum flour and MOCAF proportions with levels of 40:60, 60:40, and 80:20, and the second factor is the noodle drying temperature with levels of 500C, 600C, and 700C. Each treatment is repeated three times. Chemical quality aspects that would be analyzed are water, ash, fiber, and protein contents. Meanwhile, the organoleptic quality analysis is conducted by the organoleptic test based on the likeness level/organoleptic hedonic test that encompasses color, aroma, texture, and flavor. The P1S1 treatment, in which the flour ratio is 40 g: 60 g with a drying temperature of 500C is the best treatment, obtaining the highest Result Value of 0.699, with the research variable criteria as follows: chewiness 5.6, (like), water content 6.6733%, flavor: 5.3 (rather like), protein content: 9.7033%, coarse fiber: 5.2233%, ash content: 0.2767%, color: 5.4 (rather like), and aroma: 5.4 (rather like)